Contemporary value and inheritance protection of taijiquan from the perspective of world intangible cultural heritage - Yang, Kejian (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: On December 17, 2020, Chinese Taijiquan was successfully listed in the Representative List of the Intangible Cultural Heritage of Humanity, which indicates that Taijiquan, which embodies the essence of eastern culture, has been further recognized by the world. However, in the process of development, it also faces severe internal crisis and external challenges. Based on this, from the perspective of the protection of the world intangible cultural heritage, this paper systematically analyzes the contemporary value of Taijiquan, and explores the feasible path for the contemporary inheritance and protection of Taijiquan. Methods: literature method; logical analysis method; systematic analysis method. Results: The inheritance and protection of intangible cultural heritage is a common problem faced by all countries in the world. Taijiquan is the quintessence of Chinese culture. It is unique in Chinese martial arts and has strong vitality. With the continuous improvement of China's international status, comprehensive strength and people's living standards, the Party and the government attach great importance to the healthy development of the country and its people. It was pointed out at the 19th National Congress that: "The health of the people is an important symbol of the prosperity of the nation and the prosperity of the country." Driven by the will of the state, Taijiquan has received wide attention among them. For example, Tai Chi can be seen in important national documents such as "Healthy China 2030" Plan Outline, "Traditional Chinese Medicine Health Service Development Plan (2015-2020)", "National Fitness Plan (2016-2020)" and "Wushu Industry Development Plan (2019-2025)". Tai chi as an important part of Chinese martial arts practiser system, in early qing, in qianlong dynasty, shanxi folk martial artist Wang Zongyue with parts "chikako encyclopedia" in yi jing tai chi Yin and Yang philosophy to explain the theoretic, into the theory of taijiquan, taijiquan this name only, as the crystallization of the wisdom of ancient Chinese health, traditional thought, such as the Chinese Taoism, doctor. It plays an important role in human life and health. In the middle of the 19th century, China was forced to open its door to the outside world due to the invasion of western powers, which led to great changes in the social structure of China. In the face of the great changes of The Times, people from all walks of life in China have been devoting themselves in different ways to save the nation. Influenced by this, Chinese martial artists set off an upsurge of "saving the country by means of military force", which promoted the development of martial arts and accelerated the formation of the schools and styles of Taijiquan marked by the surname. With the advent of modern Chinese society and the opening of China's door to the world, the traditional Chinese philosophy attracted the attention of western philosophers, which laid an ideological foundation for the spread of Taijiquan in the western society and even the whole world. Taking the spread of Taijiquan in the UK as an example, studies show that Taijiquan culture began to spread in the UK before the 1950s, and was welcomed by many British people under the promotion of Gerda Geddes, Paul Crompton, John Kells, Zhu Jingxiong and other places, which changed the living habits of British people to a certain extent. Bring them exercise to improve their health. With the progress of science and technology, the development of The Times, taijiquan fitness, the importance is given to the function such as health care, culture, tai chi as the Chinese excellent traditional culture contains the rich tradition of philosophy, the thought origin, Lao tze thought in the form of "reactionary and weak in" thinking as the foundation of practice, can guide our life in dealing with the problems, and to the "natural harmony" as the idea, It can correct the deviation of contemporary social development and promote the revival of Chinese excellent traditional culture by the form of "the integration of arts and Taoism". At the same time, the formation of tai chi chuan is a combination of ancient guided and deep breathing technique and the related content of TCM theory, has many characteristics, such as soft, soothing, according to the related research at home and abroad show that long-term practicing taijiquan in preventing cardiovascular disease, enhance immune function, improve sports ability, improve balance ability, adjust the psychological health, and promote social interaction plays an important role in such aspects. In recent years, the protection of intangible cultural heritage has been an important topic of national and world attention. However, Taijiquan, as an excellent traditional Chinese culture, is still helpless and hesitant in the face of the development of The Times. Therefore, the state has strengthened the inheritance and protection of Taijiquan. From 2006, young's taijiquan to be included in the national first batch of intangible cultural heritage list in 2020 taijiquan success on human intangible cultural heritage representative list can be seen that tai chi chuan has been effective protection of the state, to the general recognition of the worldwide at the same time, but there is no denying that its development is faced with severe crisis internal and external challenges. Internal crisis: 1) Lack of original protection: Tai chi from the beginning of the creation to "combat" as the fundamental, fitness, feelings, and other functions is under attack and function, but now in order to meet the demand of the public to weaken the function of "art", is beneficial to promote the development of taijiquan, but lose its fundamental characteristics, at the same time in order to promote the spread of taijiquan, In the process of communication, many communication subjects pay more attention to the technical communication in the form of quantification, but ignore the interpretation and inheritance of the culture and theory of Taijiquan. 2) Imbalance of audience groups: Tai chi as a national traditional sports has a very high generality, deserve different age groups, but from the current survey the audience distribution is very uneven, in Beijing, for example, in one survey found that tai chi participants of the elderly over the age of 46 accounted in 78.7%, showing the trend of aging, In the young group, the audience is small, which is not conducive to the promotion and popularization of Taijiquan. 3) Inadequacies and deviations in functional cognition: as an excellent traditional Chinese culture, Taijiquan is similar to calligraphy, painting and temperament, etc. It pursues a kind of skill and attack realm of "four to two strokes, the last to strike, the first to come", and finally reaches the realm of "gods". Taijiquan is a kind of boxing with soft strength and strike after the attack. Its one move and one form fully show the offensive and defensive characteristics, but it can only be obtained by actual combat training on the basis of correct plate frame, and it should not be regarded as "fake" just because of the defeat in actual combat. The technical movements of Taijiquan are soft and gentle, firm and soft, and dynamic and dynamic, emphasizing light, slow and soft, while modern fighting pays attention to fast, heavy, accurate and fierce. There are extremely obvious differences between the two in technical movements. If the traditional Taijiquan is required by modern fighting, it will cause the deficiency and deviation in the cognition of the function of Taijiquan. 4) Limitation of space for inheritance: With the development of modern Taijiquan, influenced by the change of times, it is faced with the serious problem of limited space for inheritance, which is mainly reflected in the extinction of living space for inheritors and the squeezing of space for transmission. With the establishment of new China, fundamental changes have taken place in Chinese traditional society structure, tai chi heritage of people system changes, especially after the reform and opening up China's urbanization can speed up and the establishment of market economy, changed the traditional rural social structure and way of life, to some extent, this caused a large number of rural heritage people system collapse; Abroad at the same time, along with a large number of sports in the rise of China, for the living space of traditional Chinese sports, tae kwon do, for example, modern most parents are willing to their children to study taekwondo, think it can help a child develop healthy physique, perseverance, but they often ignore their country's traditional wushu education role. Under the dual influence of the inheritors and foreign sports, Chinese traditional wushu often encounters difficulties in its modern inheritance. 5) lack of policy and main body: in 2006, tai chi has been included in the national first batch of intangible cultural heritage list, but some places for sports non-material cultural heritage protection but it has not been on the agenda, not yet a systemic non-material cultural heritage protection legal system, at the same time the protection of tai chi chuan the lack of corresponding measures and policies. For example, some functional departments of local governments show an attitude of inaction and unwillingness to protect traditional national sports, and at the same time, their financial support is weak, which makes it difficult to effectively solve the practical problems faced by the inheritance of Taijiquan. The causes of the plight of the inheritance and protection of Taijiquan are complex and changeable. To fundamentally solve this complex problem, we need to update our ideas, integrate all social forces, and actively seek good solutions to the problem. Conclusion: Taijiquan is a Chinese quintessence, with art, education, culture, health, fitness, and other functions, in all aspects of people's life to be able to play a crucial role, but with the development of the era, tai chi in the process of inheritance is facing enormous challenges, in the face of such situation, this study proposed the following measures in order to offer reference for tai chi heritage protection. 1) Explore the true function: Tai chi as an unarmed combat operation from the beginning of creation and attack as the "root", as "source", however, from modern for taijiquan hardly found in the related explanation of the "art" meaning, this is the modern wushu development for a long time to the result of "art", "art" is the true function of tai chi chuan, "health" and "performance" function is to extend it, The contemporary heritage of Taijiquan can only promote its own development by returning to its original appearance. Taijiquan has the characteristics of subduing the strong with the soft and overcoming the strong with the weak, which is the result of the integration of traditional Chinese philosophy and traditional fighting techniques, and is the materialization and sublimation of the traditional fighting techniques. Therefore, we should not ignore the development of its fighting functions while inheriting the Taijiquan culture. 2) Discovering the inheritance function of Tai Chi culture: The boxing theory of Tai Chi contains rich traditional Chinese philosophical thoughts. With the end of the era of cold weapons, the role of Tai Chi in cultural inheritance is more and more prominent. Taiji culture emphasizes "the way of change" and "the method of tolerance", and attaches great importance to the thought of "harmony". It fully shows the way of change by using one move and one formula to respond to all changes and good follows the changes. The emphasis on "tolerance" and "harmony" highlights the traditional Chinese philosophy of life. Therefore, Taiji culture should be deeply explored and sorted out in contemporary times to enhance its cultural inheritance function of The Times. 3) Constructing multiple inheritance protection mechanism: The inheritance of Taijiquan is inseparable from the realization of the function of the inheritor and the expansion of the inheritance space. Therefore, strengthen the protection for inheritance people spectrum and the development of tai chi industry, first of all, the government and society should be to strengthen the explore of tai chi succession of people and protection, and establish the system of perfect non-material cultural heritage protection law, to improve the environment of folk inheritance of inheritance, at the same time, strengthen the spread of taijiquan in the school, to enhance the heritage foundation of tai chi chuan, And systematic construction of Taijiquan communication personnel training system. Secondly, to establish a perfect Tai Chi industry, the government should provide corresponding policy support and financial assistance to the Tai Chi cultural industry, and at the same time, use market means to expand its own inheritance space, establish a perfect access and management mechanism, and regulate the market order. 4) Innovation of communication methods: with the continuous progress of The Times, modern media show a trend of diversified development, especially the rapid development of media in recent years, which makes the transmission of information more rapid. Today the mainstream media carrier are mainly trill, weibo, WeChat, etc., the mainstream media software has the characteristics of real-time, randomness, convenience, simple operation, rich in content has a broad audience, taijiquan contemporary inheritance should make full use of the development of science and technology achievements, use different ways to spread itself. 5) Improve the Taijiquan competition system, to establish the system of developing the sports event in NBA games, for example, after years of development has built a system, scientific, perfect competition system and operation system, and through the commercial operations to the global spread and are popular with fans from all over the world, therefore, contemporary development of tai chi can draw lessons from the development model, Based on the perfect competition system, through the means of commercial operation and diversified communication methods, the Taijiquan competition system with its own characteristics has been created, so as to attract the attention and participation of sports fans from all over the world, and promote the contemporary inheritance and development of Taijiquan.